EKSPLORASI KEARIFAN LOKAL SASAK SEBAGAI SUMBER BELAJAR PPKn SEKOLAH MENENGAH PERTAMA - Sumardi, Lalu; Fauzan, Ahmad; Kurniawansyah, Edy; Hudori, Ahmad; Sakban (Kajian Moral dan Kewarganegaraan, 2025)
Civics subjects develop three important domains in students, namely: attitudes, skills and knowledge. One of the instruments in learning that contributes to developing these three domains is learning resources. One of the learning resources relevant to PPKn is the local wisdom of the Indonesian people. This study aims to explore Sasak local wisdom that can be used as a learning resource and its relevance to junior high school PPKn material. The approach used in this research is a qualitative approach. The type of research is classified as ethnograpy research. Data collection was carried out using interview and documentation techniques. The collected data were then analyzed using an interactive model consisting of: data condensation, data display, and conclusion drawing. The findings of this study are that all junior high school PPKn materials are relevant to Sasak local wisdom. That is, every junior high school PPKn material can use Sasak local wisdom as a learning resource. The form of relevance consists of two types, namely; content relevance (substantive) and value relevance (valuative). Substantive relevance means that Sasak local wisdom is relevant to junior high school PPKn material. The valuative relevance means that the values in Sasak local wisdom are relevant to the values in PPKn junior high school. So, it can be concluded that Sasak local wisdom can be a learning resource for junior high school in PPKn subject that can develop students' knowledge and character.